Combined Modality Therapy for Thoracic and head and Neck Cancers: A Review of Updated Literature Based on a Consensus Meeting. Issue 5 (September 2016) - Franco, Pierfrancesco; Fiorentino, Alba; Dionisi, Francesco; Fiore, Michele; Chiesa, Silvia; Vagge, Stefano; Cellini, Francesco; Caravatta, Luciana; Tombolini, Mario; De Rose, Fiorenza; Meattini, Icro; Mortellaro, Gianluca; et al.
Purpose: Combined modality therapy is a mainstay option for thoracic malignancies and head and neck cancers. The integration of different strategies is based on the multidisciplinary approach of modern clinical oncology. Radiation oncologists have to be educated, trained, and updated to provide state-of-the-art care to cancer patients and thus educational meetings are crucial. Methods: The Italian Association of Radiation Oncology Young Members Working Group (AIRO Giovani) organized its 8 th national meeting, focused on combination therapy in lung, esophageal, and head and neck cancer (with a specific focus on larynx-preservation strategies for larynx/hypopharynx tumors), involving young professionals working in Italy. The meeting was addressed to young radiation oncologists, presenting state-of-the-art knowledge, based on the latest evidence in this field. We performed a review of the current literature based on the highlights of the Congress. Results: The multimodality approach of head and neck and thoracic malignancies includes surgery, chemotherapy, and radiotherapy, but also has to take into account new information and data coming from basic and translational research and including molecular biology, genetics, and immunology. All these aspects are crucial for the treatment of non-small-cell lung cancer and esophageal, esophagogastric junction, and larynx/hypopharynx malignancies. The integration of different treatments in the clinical decision-making process to combine therapies is crucial. Conclusions: Combination therapy has proved to be a consolidated approach in these specific oncologic settings, highlighting the importance of multimodality management in modern clinical oncology. Dedicated meetings on specific topics are helpful to improve knowledge and skills of young professionals in radiation oncology.